SALES TAX COMPLIANCE AND ITS DETERMINANTS IN MALAYSIA - Tee Leap Sing; Zainol Bidin (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
Tax compliance behaviour has been addressed as a continuous serious concern globally. However, empirical research on sales tax compliance in Malaysia is still scarce. The present study can be considered a first attempt that was conducted in the context of sales tax version 2.0 for sales tax compliance in Malaysia. The main objective of this study was to investigate the determinants of sales tax compliance behaviour among Small and Medium Enterprises (SMEs) in Malaysia. The studies used the Fischer model as a basic model with the inclusion of socio-psychological factors (tax complexity, peer influence, tax fairness, tax knowledge, service quality, and compliance cost) and economic factors (tax complexity) with sales tax compliance. As a new contribution to tax compliance knowledge, the relationship between tax compliance behaviour and its determinants was also examined. Using the samples collected from employees who are working in SMEs under the manufacturing sector, findings show that tax complexity, tax fairness, peer influence, and tax knowledge have significant influences on compliance behavior. Meanwhile tax law and enforcement, service quality and compliance cost variable on tax compliance were non-significant. This study concluded with the theoretical and practical implications for the tax authority and the government of Malaysia.